2020
DOI: 10.1186/s12879-020-05242-w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between disease severity and clinical and biochemical characteristics of 143 cases of COVID-19 in Wuhan, China: a descriptive study

Abstract: Background: Coronavirus disease 2019 (COVID-19) is a novel infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in Wuhan and has quickly spread across the world. The mortality rate in critically ill patients with COVID-19 is high. This study analyzed clinical and biochemical parameters between mild and severe patients, helping to identify severe or critical patients early. Methods: In this single center, cross-sectional study, 143 patients were included and divi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
137
2
12

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(180 citation statements)
references
References 16 publications
29
137
2
12
Order By: Relevance
“…The fatal outcomes are correlated with the age of more than 65 years, pre-existing underlying diseases, the presence of secondary infections and the rises in blood in ammatory indicators. The disease severity is correlated with underling diseases such as diabetes, renal disease, and chronic pulmonary disease and abnormality of higher white blood cell counts, lower lymphocyte counts, and increased C-reactive protein [13][14][15]. Based on a solved epidemic in this study, we also found that the age and underlying comorbidities were the major factors associated with the disease severity.…”
Section: Benign Outcomes-associated Factors In Treatmentssupporting
confidence: 53%
See 1 more Smart Citation
“…The fatal outcomes are correlated with the age of more than 65 years, pre-existing underlying diseases, the presence of secondary infections and the rises in blood in ammatory indicators. The disease severity is correlated with underling diseases such as diabetes, renal disease, and chronic pulmonary disease and abnormality of higher white blood cell counts, lower lymphocyte counts, and increased C-reactive protein [13][14][15]. Based on a solved epidemic in this study, we also found that the age and underlying comorbidities were the major factors associated with the disease severity.…”
Section: Benign Outcomes-associated Factors In Treatmentssupporting
confidence: 53%
“…The age of more than 65 years, pre-existing underlying diseases, the presence of secondary bacterial infections and the rises in blood in ammatory indicators are predictors of fatal outcomes. In addition, some studies have shown that patients with severe infection are more likely to have diabetes, renal disease, and chronic pulmonary disease and have higher white blood cell counts, lower lymphocyte counts, and increased C-reactive protein [13][14][15]. The intensive care unit admission is predicted by raises in leukocyte count, alanine aminotransferase, aspartate transaminase, lactate dehydrogenase and procalcitonin [16].…”
Section: Introductionmentioning
confidence: 99%
“…retrospective and prospective observational studies [12,15,31,32,[35][36][37]. There are also reports that eosinophil remains stable in severe COVID-19 patients [13,29,38,39].…”
Section: Persistent Eosinopenia After Admission Was Associated With Cmentioning
confidence: 98%
“…[15][16][17][18][19][20][21][22][25][26][27][28]31 (Figure 3(a)) in 16 studies. [11][12][13][14]16,18,19,[21][22][23][25][26][27][28]31,34 (Figure 4(a)). [16][17][18][19][20][21][22][23][25][26][27]31 Figure 5) in 10 studies.…”
Section: Elevated Crp and Outcomementioning
confidence: 99%